2017
DOI: 10.20960/nh.487
|View full text |Cite
|
Sign up to set email alerts
|

Association between meal intake behavior and blood pressure in Spanish adults

Abstract: This study suggests that SBP/DBP might be reduced by the intake of an afternoon meal. However, population-based prospective studies are needed in order to confirm the consequences of the investigated associations on health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Epidemiological studies suggest meal timing or time of energy intake has a relationship with obesity [10,14,26,27], blood pressure [12,28,29], and type 2 diabetes [10,30], but study examining time-of-day patterns of energy intake in relation to insulin resistance is lacking. The "Evening dominant pattern" observed in the present study was associated with higher insulin resistance risk, compared with the "Noon dominant pattern", after adjusting for sociodemographic, lifestyle, and other cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest meal timing or time of energy intake has a relationship with obesity [10,14,26,27], blood pressure [12,28,29], and type 2 diabetes [10,30], but study examining time-of-day patterns of energy intake in relation to insulin resistance is lacking. The "Evening dominant pattern" observed in the present study was associated with higher insulin resistance risk, compared with the "Noon dominant pattern", after adjusting for sociodemographic, lifestyle, and other cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association between breakfast intake and hypertension, and the results are inconsistent. Two cross-sectional studies have shown that breakfast consumption was not significantly associated with hypertension [18,19]. Data from the 1946 British birth cohort showed that energy intake at breakfast at age 43 years was not significantly associated with the incidence of hypertension at age 53 years [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study, in the same cohort, found no association between time of day macronutrient intakes and BP [39]. Keller et al found that the consumption of an afternoon meal, but not other conventional Spanish meals, was modestly associated with lower SBP and DBP, even after adjustment for dietary intake and waist circumference [22]. In the present study, a temporal eating pattern characterized by having a later “lunch” meal was associated with SBP, DBP, and hypertension prevalence among women, after adjustment for potential covariates, BMI, and diet quality.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal distribution of EO in relation to BP has rarely been examined [21, 22]. In the UK Cohort Study, Almoosawi et al [21] found a positive association for higher total energy intake in the evening with 10-year increases in SBP and DBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation